Enteropancreatic reflexes mediating the pancreatic enzyme response to nutrients - Niebergall-Roth, Elke; Singer, Manfred V. (Autonomic neuroscience, 2006)
The observation that in dogs electrical stimulation of the vagus nerve elicited a strong secretory activity of the pancreas, prompted I. P. Pavlov in 1888 to conclude that the pancreatic secretory response to nutrients is mediated by enteropancreatic reflexes involving the vagus nerves. It took, however, more than 90 years until by studying the latency of pancreatic amylase response to exogenous and endogenous stimuli for the first time experimental evidence was provided for the actual existence of cholinergic vago-vagal enteropancreatic reflexes. Follow-up studies, based on stepwise extrinsic denervation of the pancreas, ruled out possible splanchnic pathways for enteropancreatic reflexes. In more recent years, experiments utilizing specific antagonists demonstrated a physiological role for both cholinergic M1 and cholecystokinin (CCK) receptors within the enteropancreatic reflex. At least a significant portion of the cholinergic fibres of the enteropancreatic reflex end on muscarinic receptors of the subtype M1. CCK, the most important hormone stimulating pancreatic enzyme secretion, appears to act at least in part on CCK receptors located on vagal afferent nerves, which in turn elicit a vago-vagal reflex, implying that CCK exerts its effect on the pancreas at least in part through vago-vagal reflexes. Furthermore, pharmacological blockade of CCK receptors totally abolished the early pancreatic amylase response to intestinal nutrients, suggesting that the activation of (probably vagal) CCK receptors is essential to run the enteropancreatic reflex.